Determinants of Foreign Ownership in LDC Manufacturing: An Indonesian Case Study - Aswicahyono, H. H.; Hill, Hal (Journal of International Business Studies, 1995)
This paper examines the determinants of foreign investment shares in the manufacturing sector of Indonesia, a large, rapidly industrializing developing country with a comparatively rich industrial database. Particular emphasis is given to the interplay between ‘industrial organization’ and ‘policy’ factors in determining these shares. Most of the industrial organization factors were found to be significantly correlated with ownership shares, although the two variables capturing intangible assets were not. Two of the three policy variables were found to be significant. Since the policy regime in developing countries is typically more interventionist than that in OECD economies, this suggests that studies of the former ignore the policy context at their peril. It is also demonstrated that the results of these types of studies are sensitive to the precise definition of ‘foreign ownership’.